Resistance Training Attenuates Activation of STAT3 and Muscle Atrophy in Tumor-Bearing Mice - Testa, Mayra Tardelli de Jesus; Cella, Paola Sanches; Marinello, Poliana Camila; Frajacomo, Fernando Tadeu Trevisan; Padilha, Camila de Souza; Perandini, Patricia Chimin; Moura, Felipe Arruda; Duarte, José Alberto; Cecchini, Rubens; Guarnier, Flavia Alessandra; Deminice, Rafael (Frontiers in Oncology, 2022)
Purpose: Although the role of signal transducers and activators of transcription (STAT3) in cachexia due to the association of circulating IL-6 and muscle wasting has been extensively demonstrated, the effect of resistance training on STAT3 in mediating muscle atrophy in tumor-bearing mice is unknown. The aim of this study is to investigate the effects of resistance exercise training on inflammatory cytokines and oxidative-mediated STAT3 activation and muscle loss prevention in tumor-bearing mice. Methods: Male Swiss mice were inoculated with Ehrlich tumor cells and exposed or not exposed to resistance exercise protocol of ladder climbing. Skeletal muscle STAT3 protein content was measured, compared between groups, and tested for possible association with plasma interleukins and local oxidative stress markers. Components of the ubiquitin-proteasome and autophagy pathways were assessed by real-time PCR or immunoblotting. Results: Resistance training prevented STAT3 excessive activation in skeletal muscle mediated by the overabundance of plasma IL-6 and muscle oxidative stress. These mechanisms contributed to preventing the increased key genes and proteins of ubiquitin-proteasome and autophagy pathways in tumor-bearing mice, such as Atrogin-1, LC3B-II, and Beclin-1. Beyond preventing muscle atrophy, RT also prevented strength loss and impaired locomotor capacity, hallmarks of sarcopenia. Conclusion: Our results suggest that STAT3 inhibition is central in resistance exercise protective effects against cancer-induced muscle atrophy and strength loss.